2020
DOI: 10.3390/ijerph17197297
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-Econometric Analysis of Urban Land Use Efficiency in China from the Perspective of Natural Resources Input and Undesirable Outputs: A Case Study of 287 Cities in China

Abstract: The rapid urbanization in China has had a huge impact on land use and the scarcity of land resources has become a constraint for sustainable urban development. As urban land is an indispensable material basis in economic development, measuring its use efficiency and adopting effective policies to improve urban land use efficiency (ULUE) are important links in maintaining sustainable economic growth. By establishing a comprehensive ULUE evaluation index system that emphasizes on incorporating the natural resour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…This is also consistent with Xue et al (2022), who showed a "U-shaped" curve relationship between economic development and ULUE in the Yellow River basin [15]. However, the relationship between ULUE and EDL is spatially heterogeneous [30], and the relationship between them may be an inverted "U-shape" in other regions, for example, Han et al (2020) found an inverted "U-shaped" relationship between economic development and ULUE at the national scale [30]. That is, as the economy grows, the efficiency of ULUE may first increase rapidly, then grow slowly, and then level off or even decline.…”
Section: Ekc "U-shaped" Curve Modelsupporting
confidence: 91%
See 2 more Smart Citations
“…This is also consistent with Xue et al (2022), who showed a "U-shaped" curve relationship between economic development and ULUE in the Yellow River basin [15]. However, the relationship between ULUE and EDL is spatially heterogeneous [30], and the relationship between them may be an inverted "U-shape" in other regions, for example, Han et al (2020) found an inverted "U-shaped" relationship between economic development and ULUE at the national scale [30]. That is, as the economy grows, the efficiency of ULUE may first increase rapidly, then grow slowly, and then level off or even decline.…”
Section: Ekc "U-shaped" Curve Modelsupporting
confidence: 91%
“…Cao et al (2019) used the GWR model to analyze the contribution of per capita GDP impact factors to improve or reduce ULUE relative to other impact factors [29]. Han et al (2020) selected the spatial econometric model to explore the significant positive significant indigenous effect between the EDL and ULUE in Central, Western, and Northeastern China, and found no significant indigenous effect between the EDL and ULUE in the eastern region, that is, there was spatial heterogeneity in the relationship between ULUE and EDL [30]. In general, there are many studies that examine EDL as one of the many influencing factors of ULUE and explore the impact of EDL on ULUE through many influencing factors using spatial econometric analysis so as to realize the research on the relationship between ULUE and EDL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study referred to the research results of Niu et al [62], Deng et al [10], and Han et al [63] to analyze the intrinsic mechanism of the effect of the N-TU on the ULUE in four paths: social urbanization, economic urbanization, demographic urbanization, and spatial urbanization (Figure 2). H2.…”
Section: Impact Mechanismmentioning
confidence: 99%
“…However, the current conditions and reality in China reflect the fact that there are more people than the land can support, land resources are scarce, utilization efficiency is low, and land use causes serious damage to the environment [5][6][7]. Therefore, the traditional extensive mode of development of industrial land can no longer meet the requirements for improving the quality and efficiency of social and Land 2022, 11, 261 2 of 22 economic development [8][9][10][11]. The report of the 18th National Congress of the Communist Party of China pointed out that land resources should be saved and used intensively.…”
Section: Introductionmentioning
confidence: 99%